2009
DOI: 10.1074/jbc.m109.013698
|View full text |Cite
|
Sign up to set email alerts
|

PR55α, a Regulatory Subunit of PP2A, Specifically Regulates PP2A-mediated β-Catenin Dephosphorylation

Abstract: A central question in Wnt signaling is the regulation of ␤-catenin phosphorylation and degradation. Multiple kinases, including CKI␣ and GSK3, are involved in ␤-catenin phosphorylation. Protein phosphatases such as PP2A and PP1 have been implicated in the regulation of ␤-catenin. However, which phosphatase dephosphorylates ␤-catenin in vivo and how the specificity of ␤-catenin dephosphorylation is regulated are not clear. In this study, we show that PP2A regulates ␤-catenin phosphorylation and degradation in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
98
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(111 citation statements)
references
References 32 publications
(35 reference statements)
9
98
1
Order By: Relevance
“…The dephosphorylation of β-catenin and its resulting translocation to the nucleus are associated with tumor grade in various cancers, including AdCC. Previous reports revealed interactions between β-catenin and PP2A (15)(16)(17). Moreover, it was shown that a specific regulatory subunit of PP2A, PR55α, directly interacts with β-catenin (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dephosphorylation of β-catenin and its resulting translocation to the nucleus are associated with tumor grade in various cancers, including AdCC. Previous reports revealed interactions between β-catenin and PP2A (15)(16)(17). Moreover, it was shown that a specific regulatory subunit of PP2A, PR55α, directly interacts with β-catenin (17).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports revealed interactions between β-catenin and PP2A (15)(16)(17). Moreover, it was shown that a specific regulatory subunit of PP2A, PR55α, directly interacts with β-catenin (17). Together with our current results on the involvement of PR55β in the Wnt/β-catenin signalling pathway, these data suggest that the regulation of β-catenin via the phosphatase activity of PP2A is driven by the inclusion of regulatory subunits of the B (PR55) class, such as PR55α and PR55β.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has demonstrated that CKI␣ regulates Drosophila embryonic development by regulating ␤-catenin phosphorylation and degradation (3). We have also demonstrated that PP2A (Twins) regulates Drosophila wing development by regulating ␤-catenin dephosphorylation (18). The Drosophila model provides a powerful tool to study Wnt/Wg signaling in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphatase 2A (PP2A) and its regulatory subunit, PR55␣, directly interact with and inhibit ␤-catenin phosphorylation (18). Whether ␤-catenin ubiquitination is also directly regulated by a deubiquitinase is not known.…”
mentioning
confidence: 99%
“…Moreover, the same regulatory subunit might target a set of diverse substrates. For example, the B55␣ (55-kDa regulatory subunit, alpha isoform) subunit has been involved in dephosphorylation of CDK1/cyclin B1 substrates during the mitotic transition (14)(15)(16), dephosphorylation of AKT (Thr308) (17), Tau protein (18), FOXO1 (forkhead box O1) transcription factor (19), EDD (a negative regulator of p53) (20), betacatenin (21), and p107 (22). The latter was also reported to be a substrate of PP2A-PR59 holoenzyme (23).…”
mentioning
confidence: 99%